The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2050312119834470
|View full text |Cite
|
Sign up to set email alerts
|

Needs management in families affected by childhood-onset dystrophinopathies

Abstract: Purpose: To collect information about the needs of families affected by childhood-onset dystrophinopathies residing in the United States. Methods: Individuals with an eligible dystrophinopathy were identified by the Muscular Dystrophy Surveillance, Tracking, and Research network. Between September 2008 and December 2012, 272 caregivers completed a 48-item survey about needs related to information, healthcare services, psychosocial issues, finances, caregiver demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Additionally, neuropsychological evaluations are recommended within the first year of diagnosis, when cognitive and behavioral concerns are first identified, and periodically as needed to track functioning . Yet, data from epidemiological studies and healthcare provider‐surveys demonstrate significant barriers that families face with adherence to standard‐of‐care guidelines. Access to specialty services and out‐of‐pocket expenses for families are key barriers to adherence .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, neuropsychological evaluations are recommended within the first year of diagnosis, when cognitive and behavioral concerns are first identified, and periodically as needed to track functioning . Yet, data from epidemiological studies and healthcare provider‐surveys demonstrate significant barriers that families face with adherence to standard‐of‐care guidelines. Access to specialty services and out‐of‐pocket expenses for families are key barriers to adherence .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, only 24% of muscular dystrophy subjects had had a neuropsychological assessment in accordance with DMD Care Considerations . Furthermore, caregivers identified unmanaged psychosocial issues as an area of unmet need . A pertinent finding from the Neuromuscular Disease Healthcare Provider Survey found that psychological health was the “number one” area of high unmet need in neuromuscular disorders, affecting nearly 90% of patients, and more than 50% of the healthcare providers reported that access to a mental health professional as extremely challenging…”
Section: Introductionmentioning
confidence: 99%